Study of Water Stagnant in Golf Driving Range - Nuraqilla Irdayu Ismail; Salleh A M (Recent Trends in Civil Engineering and Built Environment, 2021)
Water stagnant due to heavy rainfall is one of the problem that could be avoid with designing the drainage and levelling the land surface properly. The research had been carried out to helping the responsible department in University Tun Hussein Onn Malaysia (UTHM) which is Pejabat Pembangunan dan Penyenggaraan (PPP). The method that use in this research are levelling, traverse and tacheometry. For the levelling method, it was to obtain the different level of surface in golf driving range. Method of traverse in this research to determine the boundaries of golf driving range and the method of tacheometry is to obtaining the topographic plan and mapping of golf driving range. Automatic levelling equipment and total station were use in this research. In this study, AutoCAD and SDR Mapping and Design software is applied to produce topographic plan in golf driving range UTHM. The result of this study shows the area of highest and lowest level in golf driving range. The highest point level in study area is 99.908 and the lowest level is 99.302. From the analysis that has been done, the caused of water stagnant in golf driving range is the surface of area had different level and the water run-off were accumulate at the lowest level. The suggestion to solve this problem are to carry out the land reclaimation at the lower level and redesign the drainage in golf driving range.